Beyond Measure: The Value of the Memorised Poem. Issue 4 (1st October 2016) - Pullinger, Debbie; Whitley, David
Abstract: For centuries, memorisation was the vital mode through which the 'uses of poetry' were realised. Mixed reactions to its reinstatement on the primary curriculum indicate how much has changed. But does memorisation afford a type of understanding not available through reading or critical analysis? This article draws on the initial findings of the Cambridge Poetry and Memory Project, which sought to identify what is distinctive about this mode of engagement. At the time of writing, we are still analysing our findings. Here we explore three emerging themes through which we are starting to make sense of these: the memorised poem experienced as a living entity; as indwelling and indwelt; and within a relationship of love. We suggest that memorisation and literary analysis may become mutually enhancing, and conclude that the memorised poem is a largely unrecognised resource with the potential to enrich people's lives in multiple ways over many years.